Effect of tamsulosin on blood glucose levels in euglycemic and alloxan induced diabetic rats and its interaction with glibenclamide - Satpute, Sumit; Nerurkar, Rajan; Kokne, Manish (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To evaluate the effect of tamsulosin on blood glucose levels in euglycaemic rats and to investigate the effect of glibenclamide, tamsulosin and their combination on alloxan induced diabetic rats. Methods: Albino male wistar rats were randomly assigned into 6 groups (2 euglycaemic and 4 alloxan induced diabetic rats groups). In Euglycaemic rats either normal saline (0.5ml P.O) or tamsulosin (0.072mg/kg P.O) were given and blood glucose levels was estimated at 0 hr, 30min, 1hr, 2hr, 4hr on day 1 and at 0hr and 1hr on day 3 and day 7. Four groups of diabetic rats were given normal saline (0.5ml P.O), glibenclamide (5mg/kg P.O), tamsulosin (0.072mg/kg P.O), combination of glibenclamide and tamsulosin respectively and blood glucose levels were estimated on day 1, 3 and 7. Repeated measures ANOVA or paired ‘t ‘test were used for within group comparison and one way ANOVA or unpaired ‘t’ test were used for between group comparison. Results: In euglycaemic rats tamsulosin caused significant rise in blood glucose levels at 1 hr on all days and in diabetic rats tamsulosin itself did not cause any significant alteration in blood glucose levels. However, its combination with glibenclamide delayed the onset of hypoglycemic effect of glibenclamide & also reduced its hypoglycemic effect. Conclusions: Tamsulosin significantly increase blood glucose level in euglycaemic rats and it interact with Glibenclamide to reduce its hypoglycemic activity in diabetic rats.